2018
DOI: 10.1186/s13071-018-2983-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies of Toxoplasma gondii transcriptomes: insights into stage conversion based on gene expression profiling and alternative splicing

Abstract: BackgroundToxoplasma gondii is one of the most important apicomplexan parasites and infects one-third of the human population worldwide. Transformation between the tachyzoite and bradyzoite stages in the intermediate host is central to chronic infection and life-long risk. There have been some transcriptome studies on T. gondii; however, we are still early in our understanding of the kinds and levels of gene expression that occur during the conversion between stages.ResultsWe used high-throughput RNA-sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 52 publications
1
14
1
Order By: Relevance
“…In the future, with formulation and pharmacokinetics of JAG21 optimized, it will be of interest to determine whether JAG21 can eliminate these organisms and any residual structures as in Figure 6C, or whether adding synergistic compounds such as atovaquone ( Figure 4B) or antisense effective against these upregulated molecular targets, such as kinases, ATPases, AP2s (Figure 6D and Supplemental Table 2), or a newly recognized bradyzoite master regulator of differentiation might be effective alone or might be synergistic with JAG21 against this RPS13, as well as the conventional recognized tachyzoite and bradyzoite life cycle stages. Chen et al reported in the transcriptomes of established bradyzoite in vivo cysts that EIF2kinase of stressed parasites is present (Chen et al, 2018), but we have not found other overlap of Chen's transciptome with P cynomogli or RPS13 transcriptomes. Others have described EIF2kinase and stress granules only in transitioning or extracellular parasites (Watts et al, 2015).…”
Section: G1 Arrest Persisters Companion Compoundscontrasting
confidence: 82%
“…In the future, with formulation and pharmacokinetics of JAG21 optimized, it will be of interest to determine whether JAG21 can eliminate these organisms and any residual structures as in Figure 6C, or whether adding synergistic compounds such as atovaquone ( Figure 4B) or antisense effective against these upregulated molecular targets, such as kinases, ATPases, AP2s (Figure 6D and Supplemental Table 2), or a newly recognized bradyzoite master regulator of differentiation might be effective alone or might be synergistic with JAG21 against this RPS13, as well as the conventional recognized tachyzoite and bradyzoite life cycle stages. Chen et al reported in the transcriptomes of established bradyzoite in vivo cysts that EIF2kinase of stressed parasites is present (Chen et al, 2018), but we have not found other overlap of Chen's transciptome with P cynomogli or RPS13 transcriptomes. Others have described EIF2kinase and stress granules only in transitioning or extracellular parasites (Watts et al, 2015).…”
Section: G1 Arrest Persisters Companion Compoundscontrasting
confidence: 82%
“…Similar limitations apply to conclusions based on transcriptomic and proteomic data. While these approaches are powerful to functionally associate genes and resolve differences of physiological states of the parasite under different conditions, such as host environments 64 and stage conversion states 75 , 76 , functional implications on the phenotype level and mechanistic insights are constrained by functional gene annotations. Combined multi-omics approaches might provide insights beyond the metabolic dimension of host–parasite interactions in the future 77 .…”
Section: Future Methods To Study Host–parasite Interactionsmentioning
confidence: 99%
“…Due to contamination with mosquito RNA, they only managed to sequence a relatively small amount of ookinete-specific RNA (0.7 million reads compared to ∼5 million reads for RNA-seq analyses of other apicomplexan stages), resulting in identification of only 15 additional alternatively spliced transcripts in this stage. A similar study of Toxoplasma also found different alternative splice events in proliferating tachyzoite stages (42 genes with alternative splicing detected using a de novo assembly detection method) compared to persistent bradyzoite stages (65 genes with alternative splicing) (43). However, as with the other work described above, this study examined splicing independently at each stage and did not test for statistically differential splicing between stages, which must be a priority for future multistage studies of splicing in Apicomplexa.…”
Section: Alternative Splicingmentioning
confidence: 82%